"... Их бин нервосо...": [повести, рассказы] / Дина Рубина - Рубина Дина (Эксмо, 2012)
Экземпляры: ФО-24 (20140411) / Инвентарный номер: 49281 / Цена: 107.40 / Сис.шифр: Р2 / Авт.знак: Р 82 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6